The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.ejcn.1601837
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering effects of plant sterol esters differ in milk, yoghurt, bread and cereal

Abstract: Objective: To measure the relative effects of each of four phytosterol ester-enriched low-fat foods (bread, breakfast cereal, milk and yoghurt) on serum lipids, plasma phytosterols and carotenoids. Design: Three research centres undertook a randomised, incomplete crossover, single-blind study consisting of four treatment periods of 3 weeks each, one of which was a control period. Each sterol-enriched test food provided 1.6 g/day of phytosterols as sterol esters. Setting: General Community. Subjects: In all 58,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 14 publications
6
101
2
2
Order By: Relevance
“…Many of the recent studies that investigated the cholesterol-lowering effect of PS or stanols incorporated into low-fat foods and beverages have reported that the food products have been taken with a meal or as part of a meal. This has been the case for the following food products: cereal and bread (Nestel et al, 2001), lemonade (Spilburg et al, 2003), milk and yoghurt (Mensink et al, 2002;Clifton et al, 2004;Thomsen et al, 2004) and orange juice (Devaraj et al, 2004). Further, a greater effectiveness of consuming plant sterols daily with every meal versus the same dose every other day has been reported in an animal study (Hayes et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many of the recent studies that investigated the cholesterol-lowering effect of PS or stanols incorporated into low-fat foods and beverages have reported that the food products have been taken with a meal or as part of a meal. This has been the case for the following food products: cereal and bread (Nestel et al, 2001), lemonade (Spilburg et al, 2003), milk and yoghurt (Mensink et al, 2002;Clifton et al, 2004;Thomsen et al, 2004) and orange juice (Devaraj et al, 2004). Further, a greater effectiveness of consuming plant sterols daily with every meal versus the same dose every other day has been reported in an animal study (Hayes et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several studies have shown that consumption of PS-enriched low-fat or nonfat foods like bread, cereals, milk, yoghurt or orange juice significantly lowered TC and LDL-C, demonstrating their cholesterol-lowering efficacy (Nestel et al, 2001;Mensink et al, 2002;Spilburg et al, 2003;Clifton et al, 2004;Devaraj et al, 2004;Thomsen et al, 2004;Noakes et al, 2005). However, a few studies have suggested that the cholesterol-lowering effect of PS may be weakened when provided as low-fat or nonfat foods and beverages (Denke, 1995;Jones et al, 2003) implying that optimal efficacy is not always achieved with such food formats.…”
Section: Introductionmentioning
confidence: 95%
“…When oxidized with cholesterol oxidase and derivatized with GP hydrazine, CID of the resulting C 4,24 -3-one GP hydrazone (II) gives a The level of the plant sterol sitosterol in serum is often used as a marker for cholesterol absorption. Sterol esters, including those of sitosterol and stigmasterol, are present in phytosterol ester enriched low-fat food products, and their consumption has been shown to reduce serum total and LDL cholesterol levels [55,56]. Conversely, phytosterol levels in plasma become elevated upon consumption of these foods [55].…”
Section: Cholesterol Cholestadienes and Side-chain Modified Cholestmentioning
confidence: 99%
“…Sterol esters, including those of sitosterol and stigmasterol, are present in phytosterol ester enriched low-fat food products, and their consumption has been shown to reduce serum total and LDL cholesterol levels [55,56]. Conversely, phytosterol levels in plasma become elevated upon consumption of these foods [55]. The CID spectra of C 4 -24␤-ethyl-3-one (III) and C 4,22 -24␤-ethyl-3-one (IV) GP hydrazones showed the common features of 3-oxo-⌬ 4 GP hydrazones (Figure 3d and Supplementary Material Figure S-4).…”
Section: Cholesterol Cholestadienes and Side-chain Modified Cholestmentioning
confidence: 99%
“…Numerous laboratory studies focused on their potential to reduce cholesterol absorption by the small intestine, [1][2][3][4] and cholesterol uptake by LDL. [5][6][7] In addition, it was reported that phytosterols prevent coronary heart disease, 8 and cardiovascular risks. [9][10][11] However, their potential to reduce the risk of cancer remains controversial.…”
Section: Introductionmentioning
confidence: 99%